Recognition of Human Emotion by Speech Processing - Bodke, R.D; Satone, M.P (International Journal of Computer Sciences and Engineering, 2025)
The emotion recognition from speech is used for in human computer interaction. Most of researchers doing research on emotion recognition using speech signal. This project attempts language emotion recognition using speech signal of English language. The emotional speech samples are stored in database and used for Training And Testing. The feature extraction MFCC, PSD and Pitch detection algorithms are used. For classification of different emotions like Angry, Happy/Joy and Normal state SVM classifier is used. The all steps are implemented using MATLAB software. Raspberry pi is used for detection of emotion on hardware This classified emotions can be used for various application areas like medical, security, military etc.